Investigating the funding success factors affecting reward-based crowdfunding projects. Issue 3 (3rd July 2019) - Yeh, Tsai-Lien; Chen, Tser-Yieth; Lee, Cheng-Chun
ABSTRACT: The issue of which factors influence the success or failure of crowdfunding projects is a critical topic, as it can bring founders sufficient financial support to realise their ideal innovation. We present a useful framework for two aspects of marketing (attraction-promotion and cognition-promotion) and four related factors to foster the success of reward-based crowdfunding ventures. We investigate this issue by analysing data collected from 323 funding projects from four crowdfunding platforms in Taiwan and Japan. We found that the cognition-promotion aspect obviously influenced funding success, because the factors it encompasses – signalling (including founder response, founder updates frequency and having a formal website) and kindness (including donation to other projects and rewarding sponsors) – are all significant in the logistic regression model. Regarding the attraction-promotion aspect, we found that the past experiences of the founder in terms of the attention factor do not influence funding success. Our study contributes to the literature on crowdfunding discussion platforms and engagement, and our empirical results provide a comprehensive message to the founders and sponsors of crowdfunding platforms.